IMPLEMENTASI METODE AS-TSAWAB WA AL-IQAB DALAM MENANAMKAN KEDISIPLINAN SISWA PADA PEMBELAJARAN AKIDAH AKHLAK DI MTS JAUHARUL IMAN DESA SENAUNG KECAMATAN JALUKO - Muhammad Hariz Majid; Sururudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of the as-tsawāb wa al-‘iqāb method in fostering student discipline in the learning of Akidah Akhlak at Madrasah Tsanawiyah Jauharul Iman Senaung Village, while identifying factors that support and hinder its implementation. The study uses a qualitative approach with a type of field research, through data collection techniques in the form of interviews, observations, and documentation involving the principal, teachers, and students. The research findings show that the method is implemented gradually and adjusted to learning conditions, with forms of rewards such as praise, applause, additional marks, and simple gifts as reinforcement of positive behavior. Meanwhile, punishment is given educationally through reprimands, coaching, additional assignments, and adjustments to attitude assessments. Supporting factors include teacher competence, the existence of class rules, and class structures that play a role in assisting supervision. Inhibiting factors include limited learning time, inconsistent application of the method in other subjects, and the influence of a family environment that does not support the formation of discipline.Keywords: learning approach, Qur'an learning, slow learners.